The role of the state monetary policy in the post-conflict economic recovery - S.I. Bulchak (Економіка, управління та адміністрування)
Introduction. This paper studies the role of the monetary policy in the economy of the state, as one of the main instruments to support it’s financial potential, both at the period of military conflict as well as in the period of recovery after it. Methodological bases are general and special methods of scientific research, including synthesis, analysis, modeling, comparison, etc. The main information sources were the resources of World Bank Open Data, the data of National Bank of Ukraine and state statistics service of Ukraine.